Proses Pengelolaan Limbah Medis Padat di Rumah Sakit Umum Mamami Kupang - Ariand Miranda Lulu; Helga J. N. Ndun; Dominirsep O. Dodo (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Mamami Kupang General Hospital as a health service facility produces medical and non-medical waste. The results of surveys carried out by infectious solid medical waste at Mamami General Hospital are usually collected from waste producing places/rooms, including the Emergency Unit (ER), laboratory, nurse station, operating room, pharmacy installation, VK room, outpatient room/polyclinic. . For the process of burning/destroying medical waste, Mamami General Hospital collaborates with PT. Wastec Internasional (destroyer) and PT. Sagraha Satya Sawahita (Carrier). The average amount of solid infectious waste produced every day is around 7 kg. This research aims to determine the process of managing solid medical waste at the Mamami Kupang General Hospital. This type of research is quantitative research, with a descriptive research design. The population in this study was the solid medical waste producing unit at the Mamami Kupang General Hospital and health workers who handled the problem under study. The technique used in this research is nonprobability sampling, namely total sampling. The research results show that the medical waste management process at Mamami Kupang General Hospital, especially in temporary shelters, still requires attention. Transportation of solid medical waste from waste generating units is not encouraged using special trolleys and the accumulation of medical waste in temporary storage areas due to the unavailability of containers.